2017
DOI: 10.1007/s00277-017-2968-z
|View full text |Cite
|
Sign up to set email alerts
|

Detection of MYD88 L265P and WHIM-like CXCR4 mutation in patients with IgM monoclonal gammopathy related disease

Abstract: A broad spectrum of diseases are associated with IgM monoclonal gammopathy, including Waldenstrom macroglobulinemia (WM), various types of B cell non-Hodgkin's lymphoma (NHL), multiple myeloma (MM), primary amyloidosis (AL), and monoclonal gammopathy of undetermined significance (MGUS); these are called IgM monoclonal gammopathy related diseases (IgM-RD). We investigated MYD88 L265P and WHIM-like CXCR4 mutations in various IgM-RD. Patients with serum immunofixation electrophoresis confirmed IgM monoclonal gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…5 Three subsequent studies have confirmed the absence or infrequent occurrence of this mutation in CAD. 6,42,43 A British flow cytometry study confirmed significant immune phenotypic differences in clonal B-cells between CAD and WM/LPL. 6 In addition to the well-known, selective IGHV4-34 heavy chain gene usage in primary CAD, a recent study found a highly restricted light chain gene usage.…”
Section: A Clonal Lymphoproliferative B-cell Disordermentioning
confidence: 87%
“…5 Three subsequent studies have confirmed the absence or infrequent occurrence of this mutation in CAD. 6,42,43 A British flow cytometry study confirmed significant immune phenotypic differences in clonal B-cells between CAD and WM/LPL. 6 In addition to the well-known, selective IGHV4-34 heavy chain gene usage in primary CAD, a recent study found a highly restricted light chain gene usage.…”
Section: A Clonal Lymphoproliferative B-cell Disordermentioning
confidence: 87%
“…While its exact role in the development of MZL is unknown, it is postulated that chronic infection (e.g., Helicobacter pylori , hepatitis C) may lead to antigen-mediated BCR signaling activation and eventual lymphomagenesis [ 15 , 16 ]. Studies suggest that MYD88 L265P plays a key role in the pathogenesis of IgM monoclonal gammopathy-related diseases [ 17 ], and it is plausible that it may be an additional mechanism of BCR activation in MZL.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to ibrutinib has been reported in WM patients who lack MYD88 L265P , and the response is less robust in patients with concurrent MYD88 L265P and CXCR4 WHIM mutations [ 9 ]. A small study suggests that the incidence of CXCR4 WHIM mutations in WM and MZL patients with MYD88 L265P mutations was not significantly different [ 17 ]. However, the latter needs confirmation in larger data sets of MZL before it can be adopted into clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Cao et al [ 22 ] investigated MYD88 and CXCR4 mutations in various IgM macroglobulinemia-associated diseases, including Waldenstrom macroglobulinemia (WM), various types of B cell non-Hodgkin’s lymphoma (NHL), MM, primary amyloidosis (AL), and monoclonal gammopathy of undetermined significance (MGUS): IgM monoclonal gammopathy-related diseases (IgM-RD). Of their cohort of 112 patients, 64 (57%) carried the MYD88 L265P mutation and 14 patients (13%) carried the CXCR4 WHIM-like mutation; MYD88 L265P in cases with WM (39/42), MGUS (8/18), NHL (14/41, including 4/13 DLBCL, 1/8 eMZL, 3/6 (sMZL), 1/4 chronic lymphocytic leukemia, 2/3 nodal (n)MZL, 1/2 MCL, 1 BL, and 1 B cell NHL that could not be classified), primary AL (2/2), and IgM-PN (1/1).…”
Section: Defining Entitiesmentioning
confidence: 99%